Pediatrics for medical students - Bernstein, Daniel, 1953-; Shelov, Steven P. (Lippincott Williams & Wilkins, a Wolters Kluwer business, 2012)
Pediatrics for Medical Students, Third Edition is the perfect companion for the pediatrics clinical clerkship, and the only textbook written specifically for third-and fourth-year medical students!